Investment Law in Papua: Between Regulatory Certainty and Protection of Indigenous Peoples' Rights - Wamafma, Wamafma; Sasea, Enny Martha; Ekakusumawati, Enni; Mukhlis, Muhammad Mutawalli (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: Investment in Papua is a strategic instrument for promoting regional development and improving community welfare. However, in practice, it often causes tension between regulatory certainty for investors and the protection of indigenous peoples' rights to land and natural resources.Purposes of the Research: This study aims to analyze the legal framework for investment in Papua, identify normative conflicts that arise between national regulations and the recognition of indigenous peoples' customary rights, and evaluate the effectiveness of existing legal instruments in ensuring legal certainty and social justice.Methods of the Research: The method used is normative legal research with legislative, conceptual, and case-based approaches.Results Main Findings of the Research: The results show that although national investment regulations have guaranteed legal certainty, their implementation in Papua still faces obstacles in the form of overlapping norms and weak implementation of indigenous peoples' rights protection. Therefore, harmonization of investment regulations with customary law is needed through an inclusive and justice-based approach, so that the interests of development and the protection of indigenous peoples can be balanced.